Pengukuran Nilai Perusahaan dengan Variabel Keputusan Investasi pada Perusahaan Property dan Real Estate - Tarmedi, Eded (Universitas Pendidikan Indonesia, 2020)
ABSTRACT ARTICLE INFO:The purpose of this research is to describe and determine the influence of Investment Decisions on Firm Value on company property and real estate listed on the indonesia stock exchange the period 2010 to 2015. The type of this research is descriptive and verifikatif with a total sample namely 11 company property and real estate listed on BEI. Proxy ios used to an investment decision use Capital Expenditure to Book Value of Asset (CAPBVA ) and value of firm depicted in Price Book to Value (PBV). The design of this research is the method of time series design with a period of research for 6 years. Based on the results of the study found that when an investment decision up the value of firm will also go up and when an investment decision down the value of firm will also fall. The difference in this study lies in the object of research, study time, measuring tools, literature used, the theory used and the results of research.